Qualitative Study on the Current State of Ethical Governance in Medical Technology Enterprises - Danna ZHU; Ping XIAO; Ping JI (Yixue yu zhexue)
This study delves deeply into the current situation and awareness of medical technology ethics governance among technology enterprises in Shenzhen. Through focus group interviews with 30 professionals from the fields of research, ethics, engineering, and management, it reveals the uneven state of ethics governance among different technology enterprises; numerous challenges, such as fragmented regulation, insufficient expertise in ethical review, a lack of skilled professionals, and unclear procedural requirements. This study suggests that the government should improve the guidelines for ethical review processes, strengthen supervision, and provide more supportive services. Enterprises should also enhance their capacity for ethical review, fostering the healthy development of medical technology enterprises.